Parametric analysis of extended hemispherical dielectric lenses fed by a broadband connected array of leaky‐wave slots. Issue 7 (1st May 2015) - Yurduseven, Ozan; Cavallo, Daniele; Neto, Andrea; Carluccio, Giorgio; Albani, Matteo
Abstract : In this study, the authors examine the properties of a broadband array of leaky‐wave slots located in the focal plane of an extended hemispherical dielectric lens, to generate several independent beams for imaging applications. The array performance is investigated over a 4:1 band. Parametric analyses are performed by varying the extension length of the lens and the off‐axis distance of the feed point. The results of these analyses provide useful guidelines for the lens design. A spectral domain approach is used to characterise the field generated by the array, while a numerically efficient physical optics algorithm is employed for the analysis of the lens. Simulations performed with Computer Simulation Technology Microwave Studio are used for the validation of the combined analysis methods.